2022
DOI: 10.1126/science.abm3282
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of particulate methane monooxygenase structure and activity in a lipid bilayer

Abstract: Bacterial methane oxidation using the enzyme particulate methane monooxygenase (pMMO) contributes to the removal of environmental methane, a potent greenhouse gas. Crystal structures determined using inactive, detergent-solubilized pMMO lack several conserved regions neighboring the proposed active site. We show that reconstituting pMMO in nanodiscs with lipids extracted from the native organism restores methane oxidation activity. Multiple nanodisc-embedded pMMO structures determined by cryo–electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(139 citation statements)
references
References 64 publications
4
122
0
8
Order By: Relevance
“…This protein does not have a UniProt ID but has an NCBI accession of WP_036287217. As a recent cryo-electron microscopy structure (PDB ID: 7S4M) of this subunit only contains six cis bonds (Koo et al, 2022), the consistency of these 10 cis bonds needs to be confirmed. The second largest number (nine) of consistent cis bonds is found in GH43 arabinofuranosidase (AXHd3) of 529 amino acids (97.6% of the full length) from Humicola insolens , which also does not have a UniProt ID.…”
Section: Resultsmentioning
confidence: 99%
“…This protein does not have a UniProt ID but has an NCBI accession of WP_036287217. As a recent cryo-electron microscopy structure (PDB ID: 7S4M) of this subunit only contains six cis bonds (Koo et al, 2022), the consistency of these 10 cis bonds needs to be confirmed. The second largest number (nine) of consistent cis bonds is found in GH43 arabinofuranosidase (AXHd3) of 529 amino acids (97.6% of the full length) from Humicola insolens , which also does not have a UniProt ID.…”
Section: Resultsmentioning
confidence: 99%
“…For copper, a resolution of 2.16 Å has been obtained and for pMMO with a zinc occupied Cu C site a structure with 2.80 Å resolution has been reported. [8,19] For the structures of the enzymes, metal-nitrogen bond lengths within a range between 2.0 and 2.1 Å have been observed. We observe CuÀ N bond lengths of 1.8 Å and 2.1 Å in 1-Cu and 1.9 Å in [1-Cu]PF 6 •2 (THF).…”
Section: Methodsmentioning
confidence: 92%
“…[6][7][8] Copper occupancy of PmoC was shown to be crucial for catalytic activity in 2019 already, [9] and very recently again by cryo-electron microscopy studies on samples that still showed catalytic activity. [8] The activity goes along with an unusually high preservation of the enzyme structure, which also enables observation of the PmoC region by imaging techniques, and that for the first time in the absence of zinc. [10] Thereby, the already widely accepted constellation of Cu C with coordination of two imidazole and one carboxylate was confirmed (see Figure 1).…”
mentioning
confidence: 99%
“…This inseparable relationship was recently demonstrated in the reconstitution of the in vitro activity of the membrane-bound particulate monooxygenase by mimicking the natural lipid environment. [68] Due to their inherent hydrophobicity, terpenes diffuse into the cell membrane presumably causing local perturbations, whereupon the enzyme reacts downregulating its activity. This regulatory function by sensing membrane integrity would be a simple tool for nature to control activity of membrane-bound enzymes as already hypothesized in 1975.…”
Section: Kinetic Comparison Of the Aac Variants And The Turnover Limi...mentioning
confidence: 99%